The Mutual Influence of Organizational Culture and SSM Applied to SISP - An Action Research Study in a Non-Profit Organisation - Bhattacharjya, Jyotirmoyee; Venable, John (University Putra Malaysia and University of Singapore, 2006)
Non-profit organizations provide a large number of services of public interest, and play an important role in Australian society and economy. These organizations can very often improve or expand services to the public through the implementation of appropriate information systems and technologies. Such implementation requires undertaking a strategic information systems planning (SISP) process, and developing a strategic IS plan. This study investigated the use of Soft Systems Methodology (SSM) to conduct a SISP process in a non-profit organization. The study shows that while the existing culture of an organization can influence the SISP process, the process itself can have a significant influence on organizational culture.